Trust no one - Krentz, Jayne Ann. (2015)
"Following up on the incredible success of River Road, New York Times-bestselling author Jayne Ann Krentz delivers another masterpiece of romantic suspense. It's no coincidence when Grace Elland finds a vodka bottle next to the lifeless body of her boss, motivational speaker Sprague Witherspoon. The bottle is a terrifying-and deliberate-reminder of the horrors of her past. Grace retreats to her hometown to regroup and tries to put everything she's learned about positive thinking into practice-a process that is seriously challenged on the world's worst blind date. Awkward doesn't begin to describe her evening with venture-capitalist Julius Arkwright. She has nothing in common with a man who lives to make money, but the intense ex-Marine does have some skills that Grace can use-and he's the perfect man to help her when it becomes clear she is being stalked. As Witherspoon's financial empire continues to crumble around them, taking a deadly toll, Julius will help Grace step into her past to uncover a devious plan to destroy not only Grace, but everyone around her"--
"New standalone romantic suspense from Jayne Ann Krentz"--
Keywords: FICTION / Romance / Suspense; FICTION / Romance / General; Romantic suspense fiction